Angiotensin II type 1 receptor blockers suppress neointimal hyperplasia after stent implantation in carotid arteries of hypercholesterolemic rabbits. (February 2015) - Ichikawa, Naoki; Toma, Naoki; Kawakita, Fumihiro; Matsushima, Satoshi; Imanaka-Yoshida, Kyoko; Yoshida, Toshimichi; Taki, Waro; Suzuki, Hidenor i.
<x content-type="archive" xml:space="preserve">Abstract</x> Objectives: The purpose of this study was to examine whether oral administration of an angiotensin II type 1 receptor blocker (ARB) inhibited in-stent neointimal hyperplasia in carotid arteries of hypercholesterolemic rabbits. Methods: Eleven male New Zealand white rabbits were subjected to endothelial injuries of the right common carotid arteries using a balloon catheter and then received chow containing 1% cholesterol for 6 weeks. A balloon-expandable stainless steel stent was subsequently inserted at the injured sites of the arteries. After stenting, five rabbits were randomly treated with an oral ARB, candesartan cilexetil (5 mg/kg per day orally), while the remaining six rabbits acted as untreated controls. Four weeks after the implantation, the rabbits were killed, followed by collection of the arteries including the stents. After careful removal of the stents, tissue sections were prepared and analyzed by morphometric and immunohistochemical methods. Results: The mean thickness of the neointima was 53·6±17·0 μm in the ARB-treated group, which was significantly reduced compared to 95·9±16·7 μm in the control group (P = 0·0012). Immunohistochemistry showed a decrease in accumulation of macrophages and tenascin-C expression in the arterial wall in the ARB-treated animals. Discussion: This study suggested that systemic administration of an ARB suppressed neointimal hyperplasia in the carotid artery following stent implantation by the anti-inflammatory effects, although the animal cohort tested was rather small. This finding implies that ARBs may be useful and practical agents for protection against in-stent restenosis in humans, and warrants further basic and clinical studies.